Treatment opportunities and future perspectives for pancreatic cancer patients with germline BRCA1-2 pathogenic variants. (November 2021) - Macchini, Marina; Centonze, Federico; Peretti, Umberto; Orsi, Giulia; Militello, Anna Maria; Valente, Maria Maddalena; Cascinu, Stefano; Reni, Michele
Highlights: Personalized treatments and predictive biomarkers of pancreatic cancer (PDAC) are still lacking. BRCA1-2 alterations increase sensitivity to platinum salts and PARP inhibitors. Alterations in alternative DNA damage response (DDR) genes may exert similar functional effects. Better understand genetic variants is crucial for improving treatments of DDR-deficient patients. Abstract: Personalized treatments and predictive biomarkers of pancreatic cancer (PDAC) are still lacking. Recently germline mutations in BRCA 1 and 2 genes, leading to homologous repair deficiency, have emerged as new targets for more specific and effective therapies, exploiting the increased susceptibility to platinum salts and PARP inhibitors. In addition to BRCA, pathogenic variants in PALB2 and in other genes involved in the DNA damage response pathway (DDR) represent potential targets, as well as their respective somatic alterations. This enlarged molecularly-selected population sharing the BRCAness phenotype, is expected to show a higher sensibility to a number of DNA damaging agents and DDR inhibitors. However, the possibility of new therapeutic opportunities for DDR defective PDAC patients has to face the lack of solid evidence about the proper type and timing of targeted-treatments, the potential combination strategies and most importantly, the lack of informations on the functional impact of each specific pathogenic variant on the DDR pathway. This review summarizes the current and near-future options for the clinical management of PDAC patients harboring a DDR deficiency, analyzing the state of the art of the indications of platinum salts and other cytotoxic agents in the advanced and early stage PDAC, the development of PARP inhibitors and the rational for new combinations with immunotherapy and cycle checkpoint inhibitors, as well as the strategy to overcome the development of resistance over treatments.